Efficacy, Safety, and Immunogenicity of an Escherichia coli-Produced Bivalent Human Papillomavirus Vaccine: An Interim Analysis of a Randomized Clinical Trial. (14th May 2019) - Qiao, You-Lin; Wu, Ting; Li, Rong-Cheng; Hu, Yue-Mei; Wei, Li-Hui; Li, Chang-Gui; Chen, Wen; Huang, Shou-Jie; Zhao, Fang-Hui; Li, Ming-Qiang; Pan, Qin-Jing; Zhang, Xun; et al.
Abstract: Background: The high cost and insufficient supply of human papillomavirus (HPV) vaccines have slowed the pace of controlling cervical cancer. A phase III clinical trial was conducted to evaluate the efficacy, safety, and immunogenicity of a novel Escherichia coli -produced bivalent HPV-16/18 vaccine. Methods: A multicenter, randomized, double-blind trial started on November 22, 2012 in China. In total, 7372 eligible women aged 18–45 years were age-stratified and randomly assigned to receive three doses of the test or control (hepatitis E) vaccine at months 0, 1, and 6. Co-primary endpoints included high-grade genital lesions and persistent infection (over 6 months) associated with HPV-16/18. The primary analysis was performed on a per-protocol susceptible population of individuals who were negative for relevant HPV type-specific neutralizing antibodies (at day 0) and DNA (at day 0 through month 7) and who received three doses of the vaccine. This report presents data from a prespecified interim analysis used for regulatory submission. Results: In the per-protocol cohort, the efficacies against high-grade genital lesions and persistent infection were 100.0% (95% confidence interval = 55.6% to 100.0%, 0 of 3306 in the vaccine group vs 10 of 3296 in the control group) and 97.8% (95% confidence interval = 87.1% to 99.9%, 1 of 3240 vs 45 of 3246), respectively. The side effects were mild. No vaccine-related serious adverse events were noted. Robust antibody responses for both types were induced and persisted for at least 42 months. Conclusions: The E coli -produced HPV-16/18 vaccine is well tolerated and highly efficacious against HPV-16/18–associated high-grade genital lesions and persistent infection in women.